Strategies to enhance access to diagnosis and treatment for Chagas disease patients in Latin America - Alonso Padilla, Julio (2019)
Introduction: Chagas disease, caused by infection with the parasite Trypanosoma cruzi, represents a huge public health problem in the Americas, where millions of people are affected. Despite the availability of two drugs against the infection (benznidazole and nifurtimox), multiple factors impede their effective usage: (1) gaps in patient and healthcare provider awareness; (2) lack of access to diagnosis; (3) drug toxicity and absence of treatment algorithms to address adverse effects; (4) failures in drug supply and distribution; and (5) inconsistent drug efficacy against the symptomatic chronic stage. Areas covered: We review new approaches and technologies to enhance access to diagnosis and treatment to reduce the disease burden. We also provide an updated picture of recently published and ongoing anti-T. cruzi drug clinical trials. Although there has been progress improving the research and development (R&D) landscape, it is unclear whether any new treatments will emerge soon. Literature search methodologies included multiple queries to public databases and the use of own-built libraries. Expert opinion: Besides R&D, there is a major need to continue awareness and advocacy efforts by patient associations, local and national governments, and international agencies. Overall, health systems strengthening is essential to ensure vector control commitments, as well as patient access to diagnosis and treatment.